PENGARUH TEKNOLOGI TERHADAP PERUBAHAN SIKAP ANAK S (SUDAH MENGENAL MAKE-UP, PACARAN, DAPAT MENGENDARAI SEPEDA MOTOR) DAN MOTIVASI BELAJAR - Umdatul Khoirot, Inka Eva Umulaili Theola Zevana Putri (Forum Ilmu Sosial, 2016)
This study discusses mengenahi change of attitude occurred in elementary school children (elementary school) like (already know the make-up, going out, can ride a motorcycle). The study was conducted at four elementary schools in the District Dalisodo Village Wagir Malang. SDN BEDALISODO I, II, III, IV. Of course, attitudes described should not happen if they see their age an average of 12-15 years. This shift is motivated by a fundamental phenomenon of globalization. Globalization brings progress in all things one of which is technology. This technology led to changes in attitude at the elementary school children which would bring negative impacts. The method used is quantitative method by distributing questionnaires in each school. It is used in order to obtain the data in the form of a picture change of attitude occurred. The result is the truth of the hypothesis that the influence of technological advances with changing attitudes elementary school children (elementary school). Participatory community empowerment in an effort to reduce the rate of early childhood behavior change is a solution that is offered as a result of the influence of technological developments.